2008
DOI: 10.1088/0960-1317/18/11/115017
|View full text |Cite
|
Sign up to set email alerts
|

Bio-implantable passive on-chip RF-MEMS strain sensing resonators for orthopaedic applications

Abstract: One out of ten bone fractures does not heal properly due to improper load distribution and strain profiles during the healing process. To provide implantable tools for the assessment of bone fractures, we have designed novel, bio-implantable, passive, on-chip, RF-MEMS strain sensors that rely on the resonance frequency shift with mechanical deformation. For this purpose, we modeled, fabricated and experimentally characterized two on-chip sensors with high quality factors for in vivo implantation. One of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…However, the microwave sensors based on metamaterial have been investigated till date, because they can offer the capability of obtaining higher Q-factors and sharper and deeper resonance dips in transmission, compared with the traditional structure sensors previously reported (Melik et al 2008). For example, the silicon-based metamaterial wireless strain sensors yield high sensitivity of 109 kHz/kgf with low nonlinearity error of less than 200 microstrain (Melik et al 2009a, b).…”
Section: Introductionmentioning
confidence: 99%
“…However, the microwave sensors based on metamaterial have been investigated till date, because they can offer the capability of obtaining higher Q-factors and sharper and deeper resonance dips in transmission, compared with the traditional structure sensors previously reported (Melik et al 2008). For example, the silicon-based metamaterial wireless strain sensors yield high sensitivity of 109 kHz/kgf with low nonlinearity error of less than 200 microstrain (Melik et al 2009a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Among their advantages is the ability to obtain higher quality factors ͑Q factors͒, and sharper and deeper dips on resonance in their transmission using SRR compared to traditional rf structures that we previously used ͑e.g., rectangular and circular coils͒. [17][18][19] This makes metamaterials very well suited for telemetric sensing applications. Furthermore, metamaterial architecture enables us to achieve higher resonance frequency shifts, leading to higher sensitivity and better linearity, compared to our previous rf sensor structures.…”
mentioning
confidence: 99%
“…The theoretical rationale of the design has been previously presented in detail for conventional spiral coil architecture. 19 Transmission through the matematerial sensor is shown as a function of the frequency parameterized with respect to the applied load in Fig. 2͑a͒.…”
mentioning
confidence: 99%
“…While MFEF may be a disadvantage factor for high power applications, it provides metamaterial essential sensitivity in the sensing technology, both in electromagnetics and beyond [1,35]. As Melik et al pointed out in [36], metamaterials can obtain sharper resonance and higher Q-factors compared with traditional structure sensors. Al-Naib et al [37] demonstrated the interaction between electromagnetic waves and substances under test for chemistry and biological applications.…”
Section: Field Enhancement and Applications In Sensingmentioning
confidence: 99%